Pengaruh Caring Perawat Terhadap Adaptasi Penderita Ca Colon Menurut Model Konsep Adaptasi Calista Roy (Di Komunitas Paliatif Wilayah Kerja Dinas Kesehatan Kota Surabaya) - Etik Lusiani; Widayani Yuliana; Emiliana Indah Eko Setyawati (Jurnal Keperawatan Muhammadiyah, 2019)
Ca Colon or colorectal cancer is a malignant disease in the area of the colon, caecum, ascending and descending colon to sigmoid with unclear prognosis and often without initial symptoms. The exact cause is not yet known, some risk factors for Ca Colon wrong diet, obesity, family history of cancer, age> 50 years, stress, rarely physical activity. In Indonesia, Ca colon in 2003 - 2007 found patients with Ca colon age <40 years increased (28.17%) with an advanced stage. Operative actions and stoma making can affect one's adaptation. Caring nurses are aimed at health promotion and helping the process of adaptation of sufferers. The purpose of the study was to identify the effect of caring nurses on the adaptation of Ca colon sufferers according to the Calista Roy adaptation concept model (in the Palliative Community of the City Health Office working area of Surabaya).Methods: Pre-experimental and analytical research design with the One-Group Pre-Test-posttest Design, conducted in August-September 2019 in the Palliative Community in the City Health Office in Surabaya. Total sample of 30 respondents using consecutive sampling techniques Data collection using interviews and statistical tests with WilcoxonResults: The total number of respondents 30 patients with Ca Colon consisted of 73.3% women and 26.7% male protests. Based on the age of 56-65 years is the largest percentage of respondents at 37.5%. Respondents after the intervention had adaptation of 70% with 100% residual stimulus and respondent's adaptation of 16.7% with 36.4% focal stimulus. Wilcoxon test results have an influence between Caring nurses (p = 0,000) with the adaptation of Ca Colon sufferers to adaptation.